AMH Regulation by Steroids in the Mammalian Testis: Underlying Mechanisms and Clinical Implications - Edelsztein, Nadia Y.; Valeri, Clara; Lovaisa, María M.; Schteingart, Helena F.; Rey, Rodolfo A. (Frontiers in Endocrinology, 2022)
Anti-Müllerian hormone (AMH) is a distinctive biomarker of the immature Sertoli cell. AMH expression is triggered as soon as Sertoli cells differentiate in the fetal testis, when it drives Müllerian duct regression, thus avoiding the existence of uterus and Fallopian tubes in the male. In these early stages of development, AMH production is regulated by specific transcription factors, independently of gonadotropins or sex steroids. Although its principal activity in sex differentiation is completed in early fetal life, AMH continues to be expressed by Sertoli cells throughout prenatal and postnatal life. The testis produces high amounts of AMH until the onset of puberty, when it declines to reach low adult levels. While FSH increases testicular AMH output by its action on immature Sertoli cell proliferation and on individual Sertoli cell AMH expression, the secretion of AMH by Sertoli cells also reflects a differential regulation exerted by intratesticular levels of androgens and estrogens. In the fetus and the newborn, Sertoli cells do not express the androgen receptor; therefore, the high intratesticular androgen concentrations do not affect AMH expression. Conversely, estrogens can stimulate AMH production because estrogen receptors are present in Sertoli cells and aromatase activity is stimulated by FSH. During childhood, sex steroids levels are very low and do not play a physiological role on AMH production. However, the elevated androgen production observed in precocious puberty results in AMH downregulation, and hyperestrogenic states upregulate AMH expression. During puberty, intratesticular testosterone has an inhibitory effect on AMH transcription, which overrides the stimulatory effects of estrogens and FSH. The patent direct effects of androgens and estrogens on AMH transcription are mediated by the classical mechanism involving the activity of ligand-bound androgen receptor and estrogen receptor α on AMH promoter sequences. A modest estrogen action is also mediated by the membrane G-coupled estrogen receptor GPER. The understanding of these complex regulatory mechanisms helps in the interpretation of serum AMH levels found in physiological or pathological conditions, which underscores the importance of serum AMH as a biomarker of intratesticular steroid concentrations.